Tumor-Induced Osteomalacia Caused by Primary Fibroblast Growth Factor 23 Secreting Neoplasm in Axial Skeleton: A Case Report - Gunjan Y. Gandhi; Aashish A. Shah; Kevin J. Wu; Vivek Gupta; Ali Reza Shoraka (Case Reports in Endocrinology)
We report the case of a 66-year-old woman with tumor-induced osteomalacia (TIO) caused by fibroblast growth factor 23 (FGF-23) secreting mesenchymal tumor localized in a lumbar vertebra and review other cases localized to the axial skeleton. She presented with nontraumatic low back pain and spontaneous bilateral femur fractures. Laboratory testing was remarkable for low serum phosphorus, phosphaturia, and significantly elevated serum FGF-23 level. Magnetic resonance imaging (MRI) of the lumbar spine showed a focal lesion in the L-4 vertebra which was hypermetabolic on positron emission tomography (PET) scan. A computed tomography (CT) guided needle biopsy showed a low grade spindle cell neoplasm with positive FGF-23 mRNA expression by reverse transcriptase polymerase chain reaction (RT-PCR), confirming the diagnosis of a phosphaturic mesenchymal tumor mixed connective tissue variant (PMTMCT). The patient elected to have surgery involving anterior resection of L-4 vertebra with subsequent normalization of serum phosphorus. Including the present case, we identified 12 cases of neoplasms localized to spine causing TIO. To our knowledge, this paper represents the first documented case of lumbar vertebra PMT causing TIO. TIO is a rare metabolic bone disorder that carries a favorable prognosis. When a lesion is identifiable, surgical intervention is typically curative.